PERANAN KURATOR TERHADAP KEPAILITAN PERSEROAN TERBATAS - Alusianto Hamonangan; Muhammad Ansori Lubis; Mhd Taufiqurrahman; Rudolf Silaban (Lembaga Penelitian dan Pengabdian Pada Masyarakat (LPPM) Universitas Darma Agung (UDA) Medan, 2021)
A limited company that is declared bankrupt does not immediately stop and dissolve but still exists as a legal entity. Under certain circumstances it still exists to run its business, as usual, a limited liability company does not go bankrupt and can still carry out its business activities. This is because the company is declared bankrupt and has an economic value that is much higher than the value of the company's assets. Because bankruptcy is actually intended for companies that have negative assets. However, the decision to continue the bankruptcy company resulted in the power of the board of directors in a limited company. However, with the bankruptcy declaration, the debtor for the sake of law loses the right to control and manage his assets which are included in the bankruptcy estate as of the day of the declaration of bankruptcy. This study uses a juridical normative method, in which all sources are taken from literature, laws and other media. In the event of a limited liability company bankruptcy, the curator has the obligation to be able to manage and settle all bankruptcy assets and keep all related documents. As a result of the law that occurs from the bankruptcy of a limited liability company, it is hoped that the management of the company will carry out their duties and authority to the maximum in order to avoid bankruptcy which results in large losses to the company, especially losses incurred to debtors.